2011
DOI: 10.1016/j.jnoncrysol.2011.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic structure of ZnWO4 nanoparticles

Abstract: Static and dynamic structure of ZnWO 4 nanoparticles, synthesized by co-precipitation technique, has been studied by temperature dependent x-ray absorption spectroscopy at the Zn K-edge and W L 3 -edge. The complementary experimental techniques, such as x-ray powder diffraction, Raman and photoluminescence spectroscopies, have been used to understand the variation of vibrational, optical, and structural properties of nanoparticles, compared to microcrystalline ZnWO 4 . Our results indicate that the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
(73 reference statements)
0
18
1
Order By: Relevance
“…it is stated that the phase is indeed ZnWO 4 , but that the crystallite size is too small to produce distinct Bragg peaks. An alternative explanation is that the precipitates investigated by Kalinko et al 63 were actually amorphous nanoparticles akin to the ones found in our study, and not ZnWO 4 nanocrystallites. Tourné-sandwich ions produce an average Zn coordination number between 5.3 and 5.7 (depending on the assumed Zn/W disorder on the sites usually occupied by W), and Kalinko et al reported an average Zn coordination number in this range.…”
Section: Resultscontrasting
confidence: 48%
“…it is stated that the phase is indeed ZnWO 4 , but that the crystallite size is too small to produce distinct Bragg peaks. An alternative explanation is that the precipitates investigated by Kalinko et al 63 were actually amorphous nanoparticles akin to the ones found in our study, and not ZnWO 4 nanocrystallites. Tourné-sandwich ions produce an average Zn coordination number between 5.3 and 5.7 (depending on the assumed Zn/W disorder on the sites usually occupied by W), and Kalinko et al reported an average Zn coordination number in this range.…”
Section: Resultscontrasting
confidence: 48%
“…The obtained information on the structure relaxation in nanosized tungstates is relevant for understanding and tuning of their functional properties [15,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…3. The experimental data for NiWO 4 and ZnWO 4 were reported elsewhere [15,16]. The photoelectron wavenumber is defined as To extract structural information, the first shell EXAFS contributions χ(k)k 2 were best-fitted using a model-independent approach [17,18] allowing the reconstruction of the true radial distribution function (RDF) G(R)…”
Section: Exafs Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 The second tungstate oxides exhibit a wolframite-type monoclinic structure where both M and W atoms are bonded to six oxygen atoms, which results in the formation of octahedral [MO 6 ]/[WO 6 ] clusters. 9,10 These differences in the coordination/structure cause defects in the crystal lattice and the appearance of photocatalytic, 11,12 photoluminescence (PL), [13][14][15][16] humidity sensor [17][18][19] and magnetic properties 20,21 as well as electronic properties for the tungstates.…”
Section: Introductionmentioning
confidence: 99%